Modified Mason type III and IV radial head fractures: results of different surgical treatments - Pogliacomi, Francesco; Schiavi, Paolo; Pedrazzini, Alessio; Nosenzo, Alessandro; Tocco, Silvio; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2015)
Background and aim. Fractures of the radial head account for 4% of all fractures and 33 % of all elbow fractures. Their treatment is somewhat challenging and diversified, especially in more complex fractures (type III and IV of modified Mason’s classification). The aim of this study was to identify the best surgical treatment for patients having sustained these latter lesions and outline possible predictive factors of worse outcomes. Material and Methods. Data were retrospectively collected for 63 patients affected by radial head fracture and operated between 2006 and 2014 at the University Hospital of Parma. In 34 patients open reduction and internal fixation (ORIF) was used, in 20 radial head arthroplasty (RHA) was the treatment choice and radial head resection (RHR) was done in the remaining 9. Clinical and radiographic assessments were done at a minimum follow-up of 1 year. Clinical evaluation was performed with the Mayo Elbow performance Score (MEPS). Results. No statistical differences were observed in either type between the MEPS of affected and unaffected elbow. Multiple regression analysis showed that modified Mason IV fractures were a predictive factor of worse outcome and that an associated coronoid fracture can lead to a higher instability of elbow. Mason IV fractures treated with primary RHA are associated to better outcomes. Conclusion. According to this retrospective clinical study, it was not possible to identify the optimal surgical treatment for Mason type III fractures. However, RHA seems to be the preferred choice for Mason type IV fractures. These latter types of lesions are associated to worse outcomes.